Perceived control variables and leisure-time physical activity of adults - Sas-Nowosielski, Krzysztof; Grabara, Małgorzata; Hadzik, Andrzej (Akademia Wychowania Fizycznego w Poznaniu)
Aim of Study. To determine whether and to what extent self-efficacy, perceived fitness competence and perceived behavioral control are related to leisure time moderate-to-vigorous physical activity in adults. Material and Methods. The study involved 532 adults (including 379 women) aged 18 to 26 years. Physical activity (PA) was measured by means of a short self-report questionnaire, being a modified version o f the very popular Godin Leisure-Time Exercise Questionnaire (GLTQ). Each level of PA was described in a manner which enabled defining it by the participants with examples of activities representative for a given category, with 9 MET criteria for vigorous activity and 5 MET criteria for moderate intensity. Perceived physical competencies were measured by a relevant subscale of the Intrinsic Motivation Inventory (IMI). Results. On average, respondents undertook 2.5 hours of MVPA. Males were more active than females, and younger persons more active than older persons. For the whole sample, self-efficacy and perceived behavioral control were the two significant predictors of MVPA. However, in the case of the latter the effect size was small. In self-efficacy a nearly linear increase from sedentary to the most active group was observed. Relationships between perceived competencies, self-efficacy and perceived behavioral control and physical activity were age dependent. The comparison between younger and older adults revealed that in the younger age group all three control variables were related to physical activity, while in the older group only self-efficacy and perceived behavioral control were significant; however, in both cases the effect sizes were weak. Conclusions. The most promising interventions to increase PA are teaching strategies to cope with barriers of physical activity and convincing people that regardless of their levels their physical fitness and motor abilities enable them to be physically active. However, while it seems true for young adults, the factors determining the physical activity of older adults and reinforcement strategies look different
Keywords: moderate-to-vigorous physical activity (MVPA); adults; behavioral control; leisure-time